Kesadaran Pedagang dalam Membayar Zakat di Pasar Sukaramai Medan - Sri Novita Hasibuan; Sutiyawati; Rizky Rmadhan Saragih; Yenni Samri Juliati Nasution (Prodi Ekomoni Syariah STAI Al Akbar Surabaya, 2026)
Abstract This study aims to find out the awareness of traders in paying zakat at the Medan Sukaramai Market. The research uses a qualitative approach with the type of field research. The research informants consisted of two Muslim traders who were selected using purposive sampling techniques. Data collection was carried out through observation, interviews, and documentation, while data analysis used qualitative descriptive techniques. The results of the study showed that the two informants had a fairly good awareness in paying zakat. This awareness is shown through the understanding that zakat is an obligation that must be fulfilled by Muslims and has social benefits for people in need. This study also found that the awareness of paying zakat is influenced by religious understanding, social environment, and sense of responsibility as a Muslim. Knowledge about zakat is obtained through family, religious lectures, and the surrounding environment which also forms the awareness of zakat. However, the informant's understanding is still more focused on zakat fitrah compared to other types of zakat. Therefore, more intensive education and socialization efforts are needed regarding zakat so that the public has a broader understanding so that the implementation of zakat can be carried out optimally. The findings of this study show that religious understanding and the social environment have an important role in shaping traders' awareness to pay zakat. Keywords: Awareness of Paying Zakat, Zakat, Traders of Sukaramai Market Medan